Controversies and Challenges in clinicopathological Profile of Primary Cutaneous Lymphomas- an Indian Perspective - Shah Kajal; Panchal Harsha; Patel Apurva; . Chinmay; Parikh Sonia (New Horizons in Medicine and Medical Research Vol. 10, 2022)
Primary cutaneous lymphomas (PCLs) are rare heterogeneous family of extra nodal non-Hodgkin’s lymphomas (NHL) originate in the skin and have no extra-cutaneous illness at the time of diagnosis. the Western world, CTCLs constitute 75%–80% of all PCLs [with mycosis fungoides (MF) as the most common type of CTCL] and CBCL 20%–25%. In a tertiary care hospital in India, we looked at the epidemiology, clinical characteristics, and therapy of several subtypes of PCLs. In our Gujarat cancer and research facility, Gujarat, India, 13 patients diagnosed with PCLs between 2010 and 2015 were retrospectively reviewed. There were 9 (69.2%) male and 4 (30.8%) female (M: F = 2.2:1). The median age was 42years. Most patients (12, 92.3%) had cutaneous T-cell lymphomas (CTCLs), one patient(1, 7.7%) had cutaneous B-cell lymphomas (CBCLs). The most common subtype was mycosis fungoides (MF) (6, 46.15%), followedby subcutaneous panniculitis-like T-cell lymphoma (SPTCL) (6, 46.15%), primary cutaneous B cell lymphoma (PCBCL) (1, 7.7%). Most patients with MF presented with early-stage disease (66.7%). The current study discovered a higher proportion of CTCL patients in the middle of their lives, with a male predominance. CTCL subtypes MF and SPTCL were prevalent.